2023
DOI: 10.1101/2023.02.20.23286188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of simultaneous uncertainty quantification for image segmentation with probabilistic deep learning: Performance benchmarking of oropharyngeal cancer target delineation as a use-case

Abstract: Background: Oropharyngeal cancer (OPC) is a widespread disease, with radiotherapy being a core treatment modality. Manual segmentation of the primary gross tumor volume (GTVp) is currently employed for OPC radiotherapy planning, but is subject to significant interobserver variability. Deep learning (DL) approaches have shown promise in automating GTVp segmentation, but comparative (auto)confidence metrics of these models predictions has not been well-explored. Quantifying instance-specific DL model uncertainty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Secondly, this study employed only one metric to quantify uncertainty. The choice was made because this metric aligns well with our threshold-based approach and was shown to be the preferred choice for GTVp segmentation tasks by Sahlsten et al [5]. Nevertheless, a broader exploration of patient-specific characteristics is required to gain a comprehensive understanding of their effects on DL segmentation model results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Secondly, this study employed only one metric to quantify uncertainty. The choice was made because this metric aligns well with our threshold-based approach and was shown to be the preferred choice for GTVp segmentation tasks by Sahlsten et al [5]. Nevertheless, a broader exploration of patient-specific characteristics is required to gain a comprehensive understanding of their effects on DL segmentation model results.…”
Section: Discussionmentioning
confidence: 98%
“…To quantify uncertainty, Sahlsten et al demonstrated that the coefficient of variation (CV) may be optimal as an uncertainty measure in OPC tumour segmentation [5]. This metric quantifies the variation of the volume across multiple predictions, and it showed to be negatively correlated with the DSC in GTVp segmentation.…”
Section: Uncertainty Quantificationmentioning
confidence: 99%
“…Importantly, ensembling (e.g., through cross-validation schemes) is becoming increasingly common for many DL solutions [9] . We have previously benchmarked ensembling under a U-net framework for uncertainty estimation in oropharyngeal cancer auto-segmentation and have shown its efficacy [10] . Interestingly, Outeiral et al use cross-validation within their study for robustness analysis; merging their cross-validation outputs into an ensemble could have improved calibration when employing their HiS metric.…”
mentioning
confidence: 99%
“…Finally, we would like to note that the proposed HiS metric, if used to measure uncertainty, may be unable to disentangle epistemic uncertainty (i.e., intrinsic model uncertainty) and aleatoric uncertainty (i.e., extrinsic statistical uncertainty) [12] . While the same can be said of general measures of entropy, there exist alternative entropy-related uncertainty metrics, like expected entropy and mutual information, that could distinguish the source of the uncertainty when combined with an approximate Bayesian approach [10] , [13] . Moreover, when the distribution of DL network parameters is assumed to be a delta distribution, e.g., in a conventional DL network, the epistemic uncertainty is implicitly assumed to be non-existent.…”
mentioning
confidence: 99%
See 1 more Smart Citation